Analysis of the Degree of Legal Independence of the Bank of Algeria under the Monetary and Banking Law No. 23-09 Using the (CWN) Index. - Kamel BASSOUR (Journal of Excellence for Economics and Management Research, 2026)
The independence of central banks is a critical topic in economics, as it reflects the degree of autonomy policymakers possess in implementing effective monetary policy. The Algerian case illustrates a banking system capable of adapting to economic fluctuations and remaining resilient in the face of crises. Using the CWN model, the independence of the Bank of Algeria is estimated at 58% under the framework of the Monetary and Banking Law No. 23-09. This level is comparable to that of central banks in other developing countries, highlighting Algeria’s progress in strengthening the institutional autonomy of its central bank and its capacity to conduct independent and credible monetary policy.